Deciphering immune microenvironment and cell evasion mechanisms in human gliomas - Rafii, Soumaya; Kandoussi, Sarah; Ghouzlani, Amina; Naji, Oumayma; Reddy, Konala Priyanka; Ullah Sadiqi, Rizwan; Badou, Abdallah (Frontiers in Oncology, 2023)
Gliomas are considered one of the most malignant cancers in the body. Despite current therapies, including surgery, chemotherapy, and radiotherapy, these tumors usually recur with more aggressive and resistant phenotypes. Indeed, the survival following these conventional therapies is very poor, which makes immunotherapy the subject of active research at the present time. The anti-tumor immune response could be considered as a prognostic factor as well since each stage of cancer development is regulated by immune cells. However, glioma microenvironment contains malignant cells that secrete numerous chemokines, cytokines, and growth factors, promoting the infiltration of immunosuppressive cells into the tumor, which limits the functioning of the immune system against glioma cells. Recently, researchers have been able to reverse immune resistance of cancer cells and thus activate the anti-tumor immune response through different immunotherapy strategies. Here we review the general concept of glioma’s immune microenvironment and report the impact of its distinct components on the anti-tumor immune response. We also discuss the mechanisms of glioma cell evasion from the immune response and pinpoint some potential therapeutic pathways, which could alleviate such resistance.